Analyzing Community Responses to HIV and AIDS : Operational Framework and Typology - Rodriguez-García, Rosalía; Bonnel, Réne; N'Jie, N'Della; Olivier, Jill; Pascual, F. Brian; Wodon, Quentin (2012)
This paper presents a framework for analyzing the community response to HIV and AIDS. On the basis of a review of the literature, six criteria are proposed for characterizing such community responses: (1) the types of organizations and structures implementing the response, (2) the types of activities or services implemented and the beneficiaries of these, (3) the actors involved in and driving community responses, (4) the contextual factors that influence community responses, (5) the extent of community involvement in the response, and (6) the extent to which community responses involve wider partnerships and collaboration.